Pre-existing CD19-independent GL7− Breg cells are expanded during inflammation and in mice with lupus-like disease. (March 2016) - Wang, Xiaoqian; Wei, Yinxiang; Xiao, He; Liu, Xiaoling; Zhang, Yu; Han, Gencheng; Chen, Guojiang; Hou, Chunmei; Zhang, Li; Ma, Ning; Shen, Beifen; Li, Yan; et al.
Highlights: GL7 − B cell pool in lupus-like mice contained substantially more Bregs. Differentiation of GL7 − B cells into Breg cells does not require CD19 or Bcl6. Pre-existing GL7 − IL-10 + Breg cells are expanded during inflammation. GL7 − Breg cells in the spleen suppressed inflammatory responses in lupus-like mice. Abstract: Interleukin 10 (IL-10)-producing regulatory B-cells (Bregs) suppress inflammatory responses that mediate autoimmune diseases. However, it is unknown whether Bregs derive from a pre-existing dedicated B-cell lineage or if any B-cell can differentiate into Bregs in response to BCR or TLR activation. GL7 + B-cells are antigen-experienced differentiated B-cells while GL7 −/lo are at an early stage of B-cell differentiation. While both GL7 −/lo and GL7 + B cells can produce IL-10, differentiation of GL7 − B-cells into Bregs does not require CD19- or Bcl6-induced signals, suggesting that BCR-induced proliferation or Ig class-switching is not necessary for generation of Breg cells. Of particular importance, we show that GL7 − Breg cells are dramatically expanded in lupus-like mice and GL7 − Bregs suppressed inflammatory responses in lupus-like mice by inducing expansion of Foxp3 + Treg cells. Taken together, these results suggest that pre-existing GL7 − IL-10 + cells are expanded during inflammation, differentiate into GL7 + Bregs and contribute to immune-regulation in lupus-like mice.